2018
DOI: 10.1002/anie.201708211
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Graphene 2D Chemistry: The Emerging Field of Molybdenum Disulfide and Black Phosphorus Functionalization

Abstract: The current state of the chemical functionalization of three types of single sheet 2D materials, namely, graphene, molybdenum disulfide (MoS2), and black phosphorus (BP) is summarized. Such 2D sheet polymers are currently an emerging field at the interface of synthetic chemistry, physics, and materials science. Both covalent and non‐covalent functionalization of sheet architectures allows a systematic modification of their properties, that is, an improvement of solubility and processability, the prevention of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
152
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 201 publications
0
152
0
3
Order By: Relevance
“…[17][18][19] Secondly, chemical functionalisation to further tailor the materials' properties on demand is currently in its infancy. [20][21][22] With few exceptions, 23,24 the covalent chemistry is currently limited to CE-1T-TMDs, which are of less interest in optoelectronic applications due to its lack of visible optical absorption or emission. In addition to the functionalisation routes involving the addition of organic molecules, 20,21 it has been shown that CE-1T-TMDs react with AuCl 3 even in the absence of additional reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Secondly, chemical functionalisation to further tailor the materials' properties on demand is currently in its infancy. [20][21][22] With few exceptions, 23,24 the covalent chemistry is currently limited to CE-1T-TMDs, which are of less interest in optoelectronic applications due to its lack of visible optical absorption or emission. In addition to the functionalisation routes involving the addition of organic molecules, 20,21 it has been shown that CE-1T-TMDs react with AuCl 3 even in the absence of additional reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…There also is the apparition of Ti 2 AlC. The following reactions are suggested + → Al Ti 5 Ti 3Ti Al 3 2 (2) + → TiAl 2 Ti 3TiAl 3 (3) + → TiAl TiC Ti AlC 2 (4) At 1200 °C, the phase of Ti 2 Al disappears while TiC and TiAl phases diminish to form Ti 2 AlC. At 1300 °C, the peaks remaining can all be linked to the Ti 2 AlC compound.…”
Section: Perspective On Common Methods For Max Phases Synthesismentioning
confidence: 99%
“…[24,86] The first method uses high-energy milling before the actual HP. [24] This method uses the elemental powders of Ti, Al, and activated C. This mixture is done by following the reaction below, aiming for 100 wt% of Ti 2 AlC, which appears to form Ti 3…”
Section: Hot-pressingmentioning
confidence: 99%
See 1 more Smart Citation
“…

Eine chemisch-reduktive Volumen-Funktionalisierung von dünnlagigem schwarzem Phosphor (BP) wurde unter Verwendung von BP-Interkalationsverbindungen entwickelt. [10][11][12] Mittlerweile wurde eine erste Reihe von Vorschriften zur nicht-kovalenten Funktionalisierung verçffentlicht, die hauptsächlich darauf abzielen, die Instabilitätv on BP gegen Wasser und Sauerstoff zu verbessern. Die kovalente Funktionalisierung wurde umfassend mit mehreren spektroskopischen Methoden sowie DFT-Rechnungen nachgewiesen;e sl iegt ein hçherer Funktionalisierungsgrad als bei neutralen Funktionalisierungsreaktionen vor.

Seit2014hatderzweidimensionale(2D)schwarzePhosphor

(BP) wegen seiner hohen p-Typ-Ladungsträgermobilitätu nd seiner modifizierbaren, direkten Bandlücke große Aufmerksamkeit auf sich gezogen.

…”
unclassified